Antisemitic conspiracy theories in the early modern Iberian world : narratives of fear and hatred - Soyer, Franc̦ois, (The Iberian Religious World, 2019)
In Antisemitic Conspiracy Theories in the Early Modern Iberian World: Narratives of Fear and Hatred , François Soyer offers the first detailed historical analysis of antisemitic conspiracy theories in Spain, Portugal and their overseas colonies between 1450 and 1750. These conspiracy theories accused Jews and conversos , the descendants of medieval Jewish converts to Christianity, of deadly plots and blamed them for a range of social, religious, military and economic problems. Ultimately, many Iberian antisemitic conspiracy theorists aimed to create a 'moral panic' about the converso presence in Iberian society, thereby justifying the legitimacy of ethnic discrimination within the Church and society. Moreover, they were also exploited by some churchmen seeking to impose an idealized sense of communal identity upon the lay faithful.